Closing-in Phenomenon in Huntington's Disease: A Neuropsychological Marker of Frontal/Executive Dysfunction. (15th March 2018) - De Lucia, Natascia; Peluso, Silvio; Roca, Alessandro; Russo, Cinzia Valeria; Massarelli, Marco; De Michele, Giovanna; Di Maio, Luigi; Salvatore, Elena; De Michele, Giuseppe
Abstract: Objective: In visuo-constructional tasks, patients may reproduce drawings near-to or superimposed on a model, showing the so-called "Closing-in" (CI), often ascribed to a defect in inhibitory control. CI has been described in neurological conditions, but no studies have explored CI in Huntington's disease (HD), a neurodegenerative disorder often involving the frontal cortical–subcortical circuits. We searched for the occurrence of CI in HD patients and systematically investigated its correlates to find a clinical marker of the frontal/executive dysfunctions in the early examination of HD patients. Method: We assessed 130 HD participants, who performed a graphic coping task and a neuropsychological, psychiatric, motor, and functional assessment. Results: CI occurred in 52/130 (40%) HD patients, with 43/52 (82.7%) superimposing their copy directly on the model. MANOVA showed that HD patients with CI scored significantly poorer on Symbol digit modality test, Stroop-color word – reading test, Stroop-color word – interference test, Trail making test – part B, and Phonological verbal fluency test. However, a logistic regression analysis revealed that the significant predictor of the occurrence of CI was the score on Stroop-color word – interference test. Conclusions: HD patients may show CI in graphic tasks, and it could be related to a defect in inhibitory control impeding the switch of attention from the model to the copying space, and releasing a default tendency which causes an attraction of hand movement towards the focus of visual attention. CI might be a useful clinical marker for the early detection of frontal/executive defects in HD patients.